THE ROLE OF CULTURAL FIGURES IN THE DEVELOPMENT OF THE CULTURE OF THE SOUTHERN REGIONS OF KARAKALPAKSTAN (TAMADDUN NURI JURNALI, 2024)
The article deals with activity and creativityof well known workers whocontribited a great contribution to the development of Art and culture of the Republic of Karakalpakstan. In this article on the basis of historical sources the author presents the development of Karakalpak cultural links in XX centuries. The first, historical importance of military scientific expedition in the appearance of scientific relations, the second, the role of study historical cultural links of Karakalpak, the third, the works progressive representatives of Karakalpak intelligentsia of art in the development of Karakalpak culture.